PENINGKATAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA MELALUI MODEL PROBLEM BASED LEARNING - Fauzia, Tsania Ismi; Suprayitno, Iswahyudi Joko; Susilawati, Padmi (Litbang PWM Jawa Tengah, 2025)
The aim of this study is to determine the improvement in students' mathematical problem-solving abilities using the Problem Based Learning model in Class XI-6 of SMA Negeri 11 Semarang. This study is a Classroom Action Research (CAR) involving 36 students of Class XI-6 as subjects. The research was conducted in two cycles, with each cycle consisting of one meeting and each meeting comprising two hours of instruction. To assess the improvement in students' mathematical problem-solving abilities, evaluations were conducted at the end of each cycle. The data obtained show that there was an improvement in students' mathematical problem-solving abilities before and after the implementation of the intervention. This is evidenced by the consistent increase in students' academic performance. The average problem-solving ability in Cycle 2, using the Problem-Based Learning model, reached the Minimum Competency Criteria (KKTP) of 75. The proportion of students achieving mastery in problem-solving abilities based on the KKTP standard also reached 75%.